A descriptive cohort study of pregnancy and parenthood in women with cystic fibrosis - Aleksandra Duffy; Susan Parker; Simon Williams; Kenneth Hodson; Simon Doe; Carlos Echevarria; Stephen J. Bourke (Clinical Medicine, 2025)
Women with cystic fibrosis (wwCF) are increasingly undertaking pregnancy. This study assessed the current state of relationships, fertility, pregnancy and parenthood in a total cohort of 217 wwCF. Overall, 64% of wwCF were in long-term heterosexual relationships, 32% were single and 4% were in same-sex relationships; 64 wwCF had 111 children; 97 (87.4%) were conceived naturally and 10 (9%) by assisted reproduction. One woman had two children by surrogacy, one couple adopted a child and six wwCF had a role as a step-parent. Of the 217 wwCF, 31 (14%) died at a mean age of 41.4 years; they had 18 children, and eight of these children (44%) were younger than 18 years old when their mother died. There was a marked increase in pregnancies associated with the introduction of CF modulator medications, from three in 2020 to 16 in 2023. There were 50 pregnancies between 2020 and 2024; 17 (34%) were not planned (five were terminated); and 15 (30%) partners did not have CF genetic tests pre-conception. There were eight miscarriages. Exacerbations of lung disease occurred in 11 (31%) completed pregnancies, gestational diabetes in 12 (34%), one gastrointestinal bleeding, and one pre-eclampsia. Delivery was by caesarean section in 14 pregnancies (40%), and four (11%) births were premature (<37 weeks gestation). Although outcomes are generally good, pre-conception planning is suboptimal, pregnancy is associated with increased complications and parenthood raises complex issues regarding prognosis. CF teams should have close links with maternal medicine services to meet the specific needs of wwCF.